Re-visioning Australian colonial Christianity new essays in the Australian Christian experience 1788-1900 - Hutchinson, Mark Peter, 1958-; Campion, Edmund (Sydney, NSW The Centre for the Study of Australian Christianity, Robert Menzies College, Macquarie University, 1994)
Includes bibliographical references.
Keywords: National characteristics, Australian; Christianity -- Australia; Australia -- civilisation